Salivary C-peptide, a useful biochemical marker for insulin-dependent diabetes mellitus (Mustansiria Dental Journal, 2018)
Abstract: Insulin-dependent diabetes mellitus (IDDM) is characterized by completedestruction of β-cells, this result in little or no production of insulin & /or Cpeptidewhich is a portion of insulin & is released in amounts equal to the insulin.C-peptide level can indicate how much insulin is being produced by the pancreas.Patients & Materials: Fifty six diabetic patients were enrolled in this study (15IDDM & 41 NIDDM). C-peptide levels in serum & saliva were estimated usingRadio-immuno assay (RIA) method, with measuring serum FBS in both groups.Results: The serum & salivary levels of C-peptide as well as serum FBS levels weremarkedly higher in NIDDM than in IDDM with a significant negative correlationbetween salivary C-peptide & FBS in IDDM group.Conclusion: Salivary C-peptide level estimation can be used as an adjunct to serumFBS to measure the amount of insulin produced by β-cells, as well as to measurethe response of insulin therapy in IDDM.